DISTINCTIONS BETWEEN BIOCHEMICAL INDICATORS OF DIFFERENT BLOOD GROUPS - Azizova, N.M.; Yuldashev , N.M. (Educational Research in Universal Sciences, 2023)
The purpose of this work is to evaluate the differences in some biochemical parameters in blood plasma of blood groups I (0), II (A), III (B) and IV (AB). Biochemical indicators were determined on a Humastar100 (Germany) biochemical analyzer. The obtained results showed that there are certain statistically reliable differences between the amounts of biochemical indicators such as albumin, glucose, cholesterol, triglyceride and urea in blood plasmas of different blood groups.